Активность нападения кровососущих мокрецов (Diptera, Ceratopogonidae) в зависимости от метеорологических условий в Левобережном Полесье УССР - Жданова, Т.Г. (Вестник зоологии, 1975)
In the left-bank Polesie of the Ukrainian SSR the flight of blood-sucking biting midges begins at the first half of May and completes at the end of September (they attack actively human beings and animals in the 3d ten-day period of May, 3d ten-day period of June and 1st ten-day period of September). Two maxima of the diurnal activity, evening and early-morning, are observed. The following factors are the principal ones determining activity of the biting midges attack: air temperature, illumination and wind velocity; relative air humidity has no essential influence.